Analises univariadas e multivariadas na classificacao de atletas de voleibol masculino - Massa, M.; Tanaka, N. I.; Berti, A. F.; Böhme, M. T. S.; Massa, I. C. M. (Revista Paulista Educação Física, 1999)
The objective of this study is to compare univariate and multivariate analysis and its eventual differences in the elaboration of a classification coefficient that could help in the long term training process and in the promotion of talent in volleyball. From results of kinanthropometric tests and measures selected in accord with the specificity of volleyball, obtained from a sample composed by male volleyball athletes participating in young and adult categories, three classification coefficients were established: a) coefficient of classification by means (CCM); b) coefficient based on standard Z score (CEZ); c) coefficient based on principal components analysis (CP). They were compared with the subjective coaches classification (CT) of participating athletes. The results show that multivariate analysis, mainly the CCM, seems to adjust better the coaches impressions, offering good perspectives to its application to further studies. The CEZ analysis shows close results to CCM but, because is doesn't consider the existence of interactions among the variables, it's more restricted and therefore limited to the complexity that involves the procedures in talent selection and promotion. full text: http://www.usp.br/eef/rpef/v13n2/v13n2p131.pdf